A proposal for modeling multilevel marketing network systems - Cortez, Daniel Mark; Daway, Rhey David; Navarro, Charles Cole. (Diliman, Quezon City College of Engineering, 2005)
The introduction of multilevel marketing during the 1980's brought about a steady surge of network marketing companies these past two decades. In general, the mechanism of network marketing revolves around the concept of direct selling. For a fee, members avail of the following: they obtain discount privileges with products affiliated with the company, . Second, they are given the right to order and sell these products as distributor. Lastly, aside from the profits of direct selling, members are also given recruitment commissions, depending on the network scheme. The success of network marketing companies in the industry can be traced to two things: from the public's perspective, there is the attraction of instant wealth which is the primary catalyst of the rapid proliferation of the company's membership base. Then, in the company's perspective, there is the increase in the company's revenue which comes from the steady increase in product movement and membership. Since most individuals perceive the world of multilevel marketing as an outsider, the general notion is that the only way to success in this field is to gain entry as a member and walk the path of a distributor or a single proprietor. However, there is another paradigm in the world of network marketing that is hidden from the public and it is here where the system's true potential lies: being the network marketing company itself. There are many difficulties encountered in the attempt to assimilate a network marketing configuration and evaluates its feasibility based on given performance measures. With this information, the entrepreneur can effectively asses what networking system is most appropriate for his business. The model shown in this paper adapts Linear Programming to formulate a model that would help in forecasting the monetary flux in a binary multilevel marketing system. The paper also shows how this model can be applied in any binary network business.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Multilevel marketing; Production engineering